The effect of special exercises according to selective attention in learning the accuracy of shooting in handball for ages (10-11) years (Journal of the College of Basic Education, 2022)
objective research to prepare special exercises in accordance with prophylactic and attention learn special exercises influence in the accuracy shooting skill handball the researchers (Maher Mohammed Awad Ameri and Mahdi Muhsin Elyas) used experimental research group experimental method in the research sample was made up of the student of primary school (Al-Mustqible ) for the fifth stage primary school age (10-11) years there were 24 students, divided into two groups (experimental and Officer) (12) student in each group.The researchers used special exercises set according to selective attention and continued research methodology for (8) weeks by two units a week, and the search results were extracted using statistical software (SPSS), and are displayed in tables and analysis , Discussed in section Four, and conclusions: that special exercises prepared according to selective attention positive impact on learning to accurately attribute the correction Shooting in handball research group demos. The researchers recommended several recommendations which addition and hopes to benefit in the future: the researchers recommend using special exercises according to selective attention by researchers to teach the skill of handball in students, and interest in terms of health and identify the students personally to be a convergence between the teacher and the student who gets such phenomenon or other.